Improvement of reliability for high-ohmic Cr–Si thin film resistors in a heat and humid environment: Removing moisture source by electrocatalytic decomposition of water. (May 2016) - Wang, X.Y.; Cheng, Q.; Ma, X.P.; Zhang, H.; Li, M.X.; Chen, T.N.; Zhang, P.; Shao, J.Q.
Abstract: The reliability of high-ohmic Cr–Si thin film resistors in a heat and humid (HH) environment is often guaranteed by packaging materials as protection layers. Our previous study shows that Cr–Si–Ni film has a better performance in HH resistance than Cr–Si film in the same experimental conditions, and the proposed hypothesis that the electrocatalytic activity of Ni in the resistive film leads to water decomposition is considered as the reason behind it. In addition, NiMo alloy film is reported to have a better electrocatalytic activity on water decomposition than Ni film. So an issue arises: will the Cr–Si film co-doped by both Ni and Mo have a better performance in HH resistance than Cr–Si film only doped by Ni? In our current full paper, Cr–Si–Ni–Mo and Cr–Si–Ni films with low temperature coefficient of resistance (TCR) were prepared and compared in the same conditions to study their performance in a HH environment, which may address the raised issue from experimental data and further verify the proposed hypothesis. Possible reasons for the experimental results were discussed. If the proposed hypothesis is true, another way may be opened up to improve the reliability of high-ohmic Cr–Si resistors in a HH environment. Highlights: Ni and Mo doped Cr-Si resistive films with a low TCR were prepared. Cr-Si-Ni-Mo film has a better HH resistance than Cr-Si-Ni film. ECC of M (M = Cr, Mo) is inhibited due to electrocatalytic synergistic effect. Electrocatalytic performance of Ni is improved by M for their d electron sharing.